2020
DOI: 10.2337/dc19-2419
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Modern Diabetes Treatments DPP-4i, SGLT-2i, and GLP-1RA in White and Asian Patients With Diabetes: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: The pathophysiology of type 2 diabetes differs markedly by ethnicity. PURPOSE A systematic review and meta-analysis was conducted to assess the impact of ethnicity on the glucose-lowering efficacy of the newer oral agents, sodium-glucose cotransporter 2 inhibitors (SGLT-2i), glucagon-like peptide 1 receptor agonists (GLP-1RA), and dipeptidyl peptidase 4 inhibitors (DPP-4i), using evidence from randomized clinical trials (RCTs). DATA SOURCES A literature search was conducted in PubMed of all randomized, placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 85 publications
0
44
0
Order By: Relevance
“…This may partially explain the lower rate of baseline metformin use and higher rate of baseline DPP-4 inhibitor use in the clinically stable cohort of the CANDLE trial. Given their safety and efficacy for glycemic control, DPP-4 inhibitors are still prescribed frequently in Asian populations with T2D, even in patients with HF [ 41 43 ]. The present study showed that the baseline use of DPP-4 inhibitors did not influence the effects of canagliflozin treatment on the clinical variables examined.…”
Section: Discussionmentioning
confidence: 99%
“…This may partially explain the lower rate of baseline metformin use and higher rate of baseline DPP-4 inhibitor use in the clinically stable cohort of the CANDLE trial. Given their safety and efficacy for glycemic control, DPP-4 inhibitors are still prescribed frequently in Asian populations with T2D, even in patients with HF [ 41 43 ]. The present study showed that the baseline use of DPP-4 inhibitors did not influence the effects of canagliflozin treatment on the clinical variables examined.…”
Section: Discussionmentioning
confidence: 99%
“…This has major implications for ethnicity-specific diabetes treatment guidelines. 33 Our study has several limitations that should be taken into account in interpreting these results. Although both CARRS and ARIC were population-based cohorts, they were assembled at different time period using different sampling methodologies, and also CARRS was purely urban, while ARIC was largely urban and suburban.…”
Section: Discussionmentioning
confidence: 89%
“…Our study failed to find differences between monotherapy and add-on therapy with SGLT-2 inhibitors or GLP-1 agonists for reducing MAGE and MBG levels in patients with diabetes. SGLT-2 inhibitors and GLP-1 agonists have the ability to improve cardiovascular outcomes and/or renal outcomes [ 1 , 7 , 8 , 9 , 38 ]; however, more studies are required to evaluate their various effects, including those on GV.…”
Section: Discussionmentioning
confidence: 99%